Mucoepidermoid Carcinoma: A Comparison of Histologic Grading Systems and Relationship to MAML2 Rearrangement and Prognosis. (July 2019) - Cipriani, Nicole A.; Lusardi, Jonathan J.; McElherne, James; Pearson, Alexander T.; Olivas, Andrea D.; Fitzpatrick, Carrie; Lingen, Mark W.; Blair, Elizabeth A.
Abstract : Mucoepidermoid carcinoma (MEC) is the most common salivary gland malignancy, but categorization is complicated by variability in grading systems and uncertain prognostic significance of MAML2 rearrangement. The aims of this study were to determine the prognostic significance of MEC grading systems and MAML2 rearrangement status. Fifty-three carcinomas originally diagnosed as MEC (45 primary; 8 recurrent) of major and minor salivary glands were graded according to modified Healey, Brandwein, AFIP, and Katabi systems. Fluorescence in situ hybridization for MAML2 rearrangement was performed. Clinical features and outcomes were recorded. Twenty-five (47%) carcinomas scored the same in all grading systems. The most common histologic feature leading to a diagnosis of intermediate grade was isolated solid growth. Brandwein assigned the highest percentage of high grade (29%) and AFIP the highest percentage of low grade (80%). MAML2 was rearranged in 37/46 (80%) cases. Forty-three (81%) were morphologically compatible with MEC, and these were more likely to be low-intermediate grade and MAML2 -rearranged. Of primary carcinomas, 6 (13%) recurred. Statistically significant univariate risk factors for recurrence included non-MEC morphology, stage T4, and high Brandwein grade. Margin status, MAML2 rearrangement, and isolated solid growth were not predictive of recurrence. A binary grading system (Brandwein high vs. low-plus-intermediate) could be considered to better reflect biological behavior in MEC. Our study confirms that MAML2 wildtype tumors more likely represent high grade non-MECs, and prior studies demonstrating worse prognosis in MAML2 -nonrearranged MECs may be diluted by high-grade non-MECs. Abstract : Supplemental Digital Content is available in the text.